Analisis Karakteristik Organoleptik, pH, dan Total Bakteri pada Yoghurt Susu Sapi - Rahmiati, Rahmiati; Situmorang, Toberni S; Simanjuntak, Helen Anjelina; Pasaribu, Sudana Fatahillah; Lestari, Wanda; Sianturi, Ayu Enjelina; Amanzino, Regina Asmara (Herbal Medicine Journal, 2025)
Yogurt is made from fermented milk with the help of lactic acid bacteria starter. Yogurt is known to contain nutrients and metabolites that are beneficial for health, such as protein, calcium, phosphorus, vitamins, lactic acid and bacteriocins. The quality of yogurt is influenced by various factors, such as incubation period (storage), substrate and starter. This study aims to analyze the organoleptic characteristics, pH value, and total bacterial colonies in cow's milk yogurt incubated for 24 hours. The type of research is descriptive quantitative with a pour plate method carried out in vitro in the laboratory. The study was carried out in 4 stages including sample preparation, making cow's milk yogurt, organoleptic testing and counting total bacteria using the TPC (total plate count) method. The results showed that the pH of the cow's milk yogurt formed after 24 hours was 4. With a characteristic sour taste, semi-solid texture and a distinctive aroma of lactic acid fermentation that is light, fresh, and not pungent. The average number of total bacterial colonies was 3.66 x 102 CFU. The test was continued by determining the hedonism scale for 15 panelists. As many as 80% said they liked it.